Composite current collector, battery cell adopting composite current collector and preparation method of battery cell

By adopting a porous structure composite fluid collection in the battery, combining copper foil and aluminum foil layers, integrating the fluid collection and separator, the problems of complex battery energy density and process are solved, high energy density and simplified process are achieved, and battery performance is improved. Security.

CN119230841APending Publication Date: 2024-12-31WANXIANG 123 CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411406556.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The weight of copper/aluminum foil current collectors in existing semi-solid state/solid state batteries accounts for a high proportion, resulting in limited battery energy density, complex process and high cost, and the electrode plate conducts electron/ion conduction path is too long, affecting battery performance.

Method used

Using a composite fluid-collection structure, including copper foil layer, glue coating layer, diaphragm layer and aluminum foil layer, the porous structure is prepared through laser drilling process, the porosity and thickness are controlled, the process is simplified and the fluid-collection and diaphragm are integrated to realize single-electrode stacking , reduce the use of diaphragm.

Benefits of technology

It improves the battery energy density and safety performance, simplifies the process, shortens the battery charging time and improves the battery's rate performance, reduces the proportion of current collector weight, and enhances the battery's heat dissipation and expansion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230841A_ABST
    Figure CN119230841A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a composite current collector, a battery cell adopting the composite current collector and a preparation method of the battery cell. The preparation method of the battery cell comprises the following preparation steps: coating one side of a copper foil layer of a composite current collector with negative electrode slurry to form a negative electrode side, baking, and rolling to prepare a pole roll; coating one side of the aluminum foil layer of the composite current collector with the positive electrode slurry to form a positive electrode side, baking and rolling to prepare a novel pole piece; laminating the negative electrode sides of the two novel pole pieces to form a single battery cell structure; superposing at least two battery cell single structures to prepare a battery cell; wherein the porosity of the diaphragm layer of the composite current collector is 30-50%; according to the battery cell process, the use amount of current collector copper foil / aluminum foil is reduced, and the energy density of the battery cell is improved; positive and negative pole piece preparation and lamination links are simplified, the manufacturing process is greatly simplified, and the efficiency is improved; the electron / ion conducting path of the pole piece is reduced, and the rate capability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a composite current collector, a battery core using the composite current collector and a preparation method thereof. Background Art

[0002] Existing semi-solid / solid-state batteries conventionally use 12μm metal aluminum foil and 6μm metal copper foil as battery current collectors. The current collectors carry active substances and collect the electrons generated by the electrochemical reaction, resulting in the function of an external circuit. The positive and negative electrodes are made separately, separated by a separator in the middle. The existing copper / aluminum foil current collector accounts for a high proportion of the weight of the battery cell, about 15-20%. Due to processing limitations, the amount of current collector cannot be further reduced, and the battery energy density is limited; moreover, the existing positive and negative electrodes of the pole pieces need to be made separately, and the production of battery cells still requires the stacking process, which is complex and costly; further, the existing process pole piece conduction electron / ion path is too long, and the preparation of high specific energy batteries requires a large thickness of the pole piece, and the battery rate performance is poor. Summary of the invention

[0003] The purpose of the present invention is to provide a composite current collector with a higher battery energy density. On the other hand, the present application provides a battery cell that only needs to make a single electrode to stack, greatly shortening the process and constructing a tighter positive and negative electrode interface.

[0004] Technical solution:

[0005] In a first aspect, the present application provides a composite current collector:

[0006] A composite current collector comprises a copper foil layer, a glue layer, a diaphragm layer, a glue layer and an aluminum foil layer in sequence; the glue layer adheres the copper foil layer and the aluminum foil layer to the diaphragm layer to form a whole; the porosity of the diaphragm layer is 30-50%.

[0007] Conventional composite current collectors are generally composed of a middle polymer layer with aluminum or copper layers on both sides as the current collectors for the positive or negative electrodes. This material is used in batteries. Due to the poor thermal conductivity of the middle polymer layer, as the battery capacity increases, the current transmitted by the single cell increases, which in turn causes the heat generation of the battery to increase. The negative effect is that the safety and electrical performance are seriously degraded. In the present application, the porosity of the diaphragm is controlled to improve the heat transfer performance of the diaphragm layer, thereby improving the safety and electrical performance of the composite current collector.

[0008] Furthermore, the thickness of the adhesive layer is 0.5-1.0 μm.

[0009] Furthermore, the thickness of the diaphragm layer is 3-25 μm, and the tensile strength is 1000-2000 kg / cm 2 , the elongation at break is 5-100%.

[0010] Furthermore, the diaphragm layer is one of PI, PP and PE.

[0011] Furthermore, the thickness of the aluminum foil layer is 1-20 μm; the aluminum foil layer has a porous structure with a porosity of 30-70%; the pore size of the aluminum foil layer is 0.1-1.0 μm, and the pore size of the aluminum foil layer is prepared by a laser drilling process.

[0012] Furthermore, the copper foil layer has a thickness of 1-20 μm; the copper foil layer has a porous structure with a porosity of 30-70%; the pore size of the copper foil layer is 0.1-1.0 μm, and the pore size of the copper foil layer is prepared by a laser drilling process.

[0013] Holes with an aperture of 0.1-1.0 μm are arranged on the aluminum foil layer and the copper foil layer, and the porosity is controlled to be 30-70%, so that the aluminum foil layer and the copper foil layer with apertures are compatible with the diaphragm with apertures, thereby improving the thermal conductivity and heat dissipation performance in the battery, improving the safety performance of the composite current collector, the battery cell, and the battery, and reducing the electrical performance attenuation of the composite current collector, the battery cell, and the battery at relatively high temperatures; further, when the battery expands internally during long-term operation, the gaps in the aluminum foil layer and the copper foil layer in the composite current collector provide a certain buffer space for the expansion of substances such as the diaphragm or the electrolyte in the battery, thereby reducing irreversible damage inside the battery, reducing the attenuation of battery performance at high temperatures, and improving the safety performance of the battery.

[0014] Furthermore, the bonding force between the copper foil layer and the adhesive layer satisfies ≥2Nm / mm; the bonding force between the adhesive layer and the aluminum foil layer satisfies ≥2Nm / mm; the length of the copper foil layer is L1, the length of the diaphragm is L3, and the length of the aluminum foil layer is L5; L1>L3, L1>L5.

[0015] In a second aspect, the present application provides a method for preparing a composite current collector:

[0016] A method for preparing a composite current collector comprises coating a binder on both sides of the diaphragm, and then hot-pressing a copper foil and an aluminum foil on the binder on the surface of the diaphragm to prepare the composite current collector.

[0017] In a third aspect, the present application provides a method for preparing a battery cell:

[0018] A method for preparing a battery cell comprises the following steps:

[0019] 1) Preparation of pole coil: coating the negative electrode slurry on one side of the copper foil layer of the composite current collector to form the negative electrode side, and rolling it up after baking to prepare the pole coil;

[0020] 2) Preparation of the novel pole piece: coating the positive electrode slurry on one side of the aluminum foil layer of the composite current collector in the pole roll to form the positive electrode side, baking and drying, and rolling up to prepare the novel pole piece;

[0021] 3) Assembly of the battery cell: stack the negative electrode sides of two new electrode sheets against each other to form a single battery cell structure; and stack at least two single battery cell structures to prepare a battery cell.

[0022] The porous middle layer of the current collector can support the active material, isolate electronic short circuits, and conduct positive and negative ions. No external diaphragm is needed in the stacking process; the porous middle layer can take on the role of the diaphragm, integrating the current collector and diaphragm components together.

[0023] In the present application, the energy density of the battery cell is improved by not using a diaphragm through structural optimization, so that the battery cell or battery can store more energy at the same weight, thereby achieving a longer driving range, which is of great significance for meeting the daily travel needs of users and reducing the number of charging times; further, high energy density batteries can provide electric vehicles with higher power output and acceleration performance, and high energy density batteries can also support faster charging speeds and shorten charging time.

[0024] In the present application, a composite current collector with good heat dissipation performance and expansion resistance is used to prepare a battery cell without a diaphragm structure. The prepared battery cell not only has a high energy density and capacity, but also has good heat dissipation performance and cycle life.

[0025] A battery cell is prepared using the battery cell preparation method of the present application.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1. By setting gaps on the aluminum foil layer and the copper foil layer, the usage of the aluminum foil layer and the copper foil layer is reduced, the weight proportion of the current collector is reduced, the energy density of the battery cell is increased, and the electrical performance and safety performance are improved.

[0028] 2. Simplify the production and stacking of positive and negative electrodes, and realize single electrode production and simple stacking, without the need for a diaphragm, greatly simplifying the process and improving efficiency.

[0029] 3. In the preparation of battery cells, no diaphragm is used, which solves the problem of long electron / ion conduction path in thick electrodes of high specific energy batteries, shortens the electron / ion conduction path of the electrode, improves battery rate performance and battery cell energy density, and thus improves electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a schematic structural diagram of a composite current collector according to Example 1 of the present invention;

[0031] Figure 2 is a schematic structural diagram of a single cell structure of Example 1 of the present invention;

[0032] Figure 3 It is a schematic diagram of the structure of the battery cell of Example 1 of the present invention.

[0033] Reference numerals:

[0034] 1. Aluminum foil layer; 2. Diaphragm layer; 3. Copper foil layer; 4. New electrode; 5. Negative electrode slurry layer; 6. Positive electrode slurry layer. DETAILED DESCRIPTION

[0035] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0036] Example 1

[0037] A battery cell, the structural schematic diagram of the battery cell is as follows Figure 3 (wherein N≥0), and its preparation method comprises the following preparation steps:

[0038] The schematic diagram of the composite current collector is shown in Figure 1 The composite current collector is obtained by adhering the copper foil layer 3 and the aluminum foil layer 1 to the diaphragm layer 2 by the adhesive layer to form a whole. The preparation process is as follows:

[0039] Step 1: Optimize the thickness of 9μm PP diaphragm, porosity of 60%, and tensile strength of 1500kgf / cm 2 , elongation at break 50%, double-sided coating of PVDF adhesive 1μm.

[0040] Step 2: Optimize the thickness of 3.5μm copper foil and use conventional laser drilling process. The laser drilling process refers to the mature process in the industry. No technical requirements are made and the void ratio is 50%.

[0041] Step 3: 4.5μm thick aluminum foil is selected and conventional laser drilling process is adopted. The laser drilling process refers to the mature process in the industry and no technical requirements are made. The porosity is 50%.

[0042] Step 4: Roll and hot-press the porous 4.5 μm copper foil and 10 μm aluminum foil onto the surface of the PP diaphragm coated with PVDF on both sides at a hot-pressing temperature of 120°C and a pressure of 120 kg to prepare a composite current collector.

[0043] 1) Preparation of pole coil: Graphite: Silicon carbon: Li-2160: CNT: CMC: PAA: SBR = 65: 30: 0.5: 0.2: 1.5: 1.5: 1.3 (mass ratio) are mixed evenly to prepare negative electrode slurry, which is coated on one side of the copper foil layer 3 of the prepared composite current collector to form a negative electrode side. The negative electrode slurry forms a negative electrode slurry layer 5, and the coating surface density of the negative electrode slurry layer 5 is 165 g / m 2 , and then rolled up after baking to prepare an extreme roll.

[0044] 2) Preparation of new electrode sheet: Ni90: LB116: ECP: PVDF = 97.2: 0.5: 1.1: 1.2 (mass ratio) are mixed evenly to prepare positive electrode slurry; the positive electrode slurry is coated on one side of the aluminum foil layer 1 of the electrode roll to form the positive electrode side, and the positive electrode slurry forms a positive electrode slurry layer 6, and the density of the positive electrode slurry layer 6 is controlled at 430g / m 2 , baked, dried and rolled to prepare a new type of electrode.

[0045] 3) Assembly of battery cells:

[0046] The negative electrode sides of the two new electrode sheets are stacked to form a single cell structure 4 (the schematic diagram of the structure is shown in FIG. Figure 2 ); at least two single cell structures are stacked without a separator in between to prepare a cell (schematic diagram of the structure as shown in Figure 3 ), in this embodiment, the number of laminated layers is 20 and the designed capacity is 6.5Ah.

[0047] Comparative Example 1

[0048] A battery cell, which differs from Example 1 in that conventional 12μm aluminum foil is used as the positive electrode current collector, and 6μm copper foil is used as the negative electrode current collector. The conventional process of slurry-coating-sheeting is adopted to prepare the negative electrode pole piece. After the pole piece is baked, 12μm PE is used as the separator, and 20 / 21 layers of small soft packs are stacked, with a designed capacity of 6.5Ah.

[0049] Experimental data:

[0050] Battery Cell FCC Capacity Ah FDC capacity(Ah) ICE% Battery cell energy density Wh / kg 3C capacity retention rate 1C / 1C cycle 500 cycles capacity retention rate Example 1 7.55 6.42 84.10% 305 89.58% 82.50% Comparative Example 1 7.54 6.31 83.68% 295 57.64% 65.60%

[0051] FCC Testing Process

[0052] After battery filling

[0053] 1) 0.01C constant voltage charging for 30 minutes

[0054] 2) 0.05C constant voltage charging to 3.65V

[0055] 3) Leave it for 24 hours

[0056] 4) 0.1C constant voltage charging to 4.25V, get the first charge FCC

[0057] 5) Leave for 24 hours

[0058] 6) 0.1C constant voltage discharge to 2.5V, get the first discharge capacity FDC

[0059] Only several embodiments of the present invention are expressed, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A composite current collector, characterized in that: It comprises a copper foil layer, a glue layer, a diaphragm layer, a glue layer and an aluminum foil layer in sequence; the glue layer adheres the copper foil layer and the aluminum foil layer to the diaphragm layer to form a whole, and the porosity of the diaphragm layer is 30-50%.

2. A composite current collector according to claim 1, characterized in that: The thickness of the adhesive layer is 0.5-1.0 μm.

3. A composite current collector according to claim 1, characterized in that: The thickness of the diaphragm layer is 3-25 μm, and the tensile strength is 1000-2000 kg / cm 2 , the elongation at break is 5-100%.

4. A composite current collector according to claim 1, characterized in that: The diaphragm layer is one of PI, PP and PE.

5. A composite current collector according to claim 1, characterized in that: The thickness of the aluminum foil layer is 1-20 μm; the aluminum foil layer has a porous structure with a porosity of 30-70%; and the pore size of the aluminum foil layer is 0.1-1.0 μm.

6. A composite current collector according to claim 1, characterized in that: The copper foil layer has a thickness of 1-20 μm; the copper foil layer has a porous structure with a porosity of 30-70%; and the pore size of the copper foil layer is 0.1-1.0 μm.

7. A composite current collector according to claim 1, characterized in that: The bonding force between the copper foil layer and the adhesive layer satisfies ≥2Nm / mm; the bonding force between the adhesive layer and the aluminum foil layer satisfies ≥2Nm / mm; the length of the copper foil layer is L1, the length of the diaphragm is L3, and the length of the aluminum foil layer is L5; L1>L3, L1>L5.

8. A method for preparing the composite current collector according to any one of claims 1 to 7, characterized in that: The adhesive is coated on both sides of the separator, and then the copper foil and the aluminum foil are hot pressed on the adhesive on the surface of the separator respectively to prepare a composite current collector.

9. A method for preparing a battery cell, characterized in that: The method comprises the following preparation steps: 1) Preparation of a pole coil: coating a negative electrode slurry on the copper foil layer side of the composite current collector according to any one of claims 1 to 7 to form a negative electrode side, and rolling it up after baking to prepare a pole coil; 2) Preparation of the novel pole piece: coating the positive electrode slurry on the aluminum foil layer side of the composite current collector in the pole roll to form the positive electrode side, baking and rolling to obtain the novel pole piece; 3) Assembly of the battery cell: stack the negative electrode sides of two new electrode sheets against each other to form a single battery cell structure; and stack at least two single battery cell structures to prepare a battery cell.

10. A battery cell, characterized in that: The battery cell is prepared by the method for preparing the battery cell of claim 9.

Citation Information

Cited By

  • Composite current collector, preparation method thereof and pole piece

    CN121307038A